1996
DOI: 10.1007/s001250050598
|View full text |Cite
|
Sign up to set email alerts
|

Protein C activation in NIDDM patients

Abstract: Alteration of the clotting system in diabetic patients is presently the focus of increasing interest due to its potential role in the pathogenesis of large and smallvessel disease in diabetes mellitus. It is believed that enhanced pro-coagulant activity is linked to the excessive cardiovascular morbidity and mortality among diabetic patients which have not been fully explained by major risk factors such as arterial hypertension, cigarette smoking and hypercholesterolaemia. Perturbance of haemostasis has also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
3
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 37 publications
1
22
3
1
Order By: Relevance
“…Equally, Asakawa et al [29] had shown that fibrinogen level was significantly higher in diabetic patients with retinopathy or nephropathy than in patients without these complications. The detection of microalbuminuria, another well-known independent indicator of much greater risk of premature death from cardiovascular complications, has been demonstrated to correlate significantly with various hemostatic variables [3,26,27,30,31]. Accordingly, some coagulation factors did not differ between the diabetic patients and control subjects.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Equally, Asakawa et al [29] had shown that fibrinogen level was significantly higher in diabetic patients with retinopathy or nephropathy than in patients without these complications. The detection of microalbuminuria, another well-known independent indicator of much greater risk of premature death from cardiovascular complications, has been demonstrated to correlate significantly with various hemostatic variables [3,26,27,30,31]. Accordingly, some coagulation factors did not differ between the diabetic patients and control subjects.…”
Section: Discussionmentioning
confidence: 88%
“…This activation of blood coagulation has recently been implicated as an important contributing factor for the occurrence of vascular complications in dia- betes [27,28]. In large epidemiological studies, the procoagulant factors (fibrinogen and factor VII) have been described as independent predictors of cardiovascular events in diabetic and nondiabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the relationship between C protein and obesity and diabetes is scarce and controversial [30,31]. The study by Vegilo did not show the relationship between BMI and the activity of C protein, nor did diabetes treatment affect its activity [31].…”
Section: Discussionmentioning
confidence: 99%
“…5 However, in pathologic conditions associated with increased consumption of protein C or deficient activation of protein C disruption of the balance between thrombin and APC occurs in favor of thrombin, resulting in excessive coagulation and inflammatory responses. 7,29 Insufficient generation of APC also occurs in the airways of patients with chronic asthma. 9 In agreement with this, in our present BA model, the concentration of APC remained unchanged, and the APC/thrombin ratio was significantly decreased in mice of the OVA group compared with the nonsensitized SAL group.…”
Section: Discussionmentioning
confidence: 99%